2023
DOI: 10.1037/dhe0000343
|View full text |Cite
|
Sign up to set email alerts
|

“It is not my fault”: Exploring experiences and perceptions of racism among international students of color during COVID-19.

Abstract: Using neoracism (Lee & Rice, 2007) as a theoretical framework, this study explored international students’ experiences, challenges, and perceptions of racism and racial discrimination during COVID-19 in the U.S. By conducting three virtual focus group interviews with 18 international students in total, we identified three key themes that encapsulated participants’ challenges and experiences of perceived racism: perceptions of racism—explicit discrimination and fear of threats, feelings of being unwelcome and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…The issue of discrimination and stigmatization against those of Chinese or East Asian descent would also be detrimental to the wellbeing of Chinese international students. Indeed, the uprising of racial prejudice toward people of Chinese or East Asian descent throughout the pandemic has been frequently reported in the literature (38)(39)(40). Racist stigmatization of ethnic and racial minorities are identified as a strong predictor of early onset of mental and psychiatric disorders in adolescents and young adults that significantly associated with elevated incidences of feelings of isolation, depression, substance abuse, and self-inflicting behaviors (29,41), and affect career development (42).…”
Section: Experiences Of Students and Factors Of Stressmentioning
confidence: 99%
“…The issue of discrimination and stigmatization against those of Chinese or East Asian descent would also be detrimental to the wellbeing of Chinese international students. Indeed, the uprising of racial prejudice toward people of Chinese or East Asian descent throughout the pandemic has been frequently reported in the literature (38)(39)(40). Racist stigmatization of ethnic and racial minorities are identified as a strong predictor of early onset of mental and psychiatric disorders in adolescents and young adults that significantly associated with elevated incidences of feelings of isolation, depression, substance abuse, and self-inflicting behaviors (29,41), and affect career development (42).…”
Section: Experiences Of Students and Factors Of Stressmentioning
confidence: 99%
“… Cheah et al (2020) found that COVID-19 experiences of racial discrimination were associated with high levels of general anxiety disorder and depressive symptoms in both children and their parents. Koo et al, (2021) explored experiences and perceptions of racism among 18 international students from six different countries using virtual focus group interviews. The participants described explicit discrimination and fear of threats, feelings of being unwelcome and unsafe, and balancing the tension between relief and isolation during quarantine.…”
Section: Covid-19 and Racial Injustices Impact On Learning And Mental...mentioning
confidence: 99%
“…In many cases, international students are those who were academically high achievers in their home countries and highly proficient in English, and many of them are selected as government-funded scholars from their home countries (Koo, Km et al, 2021). However, those with the excelled English skills and academic competence are not considered as good in their host country as they were in their home countries and many international students immediately get frustrated that they cannot understand the lectures, class activities, and class discussions in their host universities (Koo, Yao et al, 2021;Koo, Kim et al, 2021). This bitter and frustrating experiences impacts international students' first impressions in their host countries as first-year international students.…”
Section: The Stories Of Comingmentioning
confidence: 99%